Primary pulmonary melanoma: the unexpected tumour - Lares Dos Santos, C (2013)
A 62-year-old woman was referred to our pulmonology team with exertional dyspnoea and chest tightness of 2 months duration. Her medical history included cervical cancer and thyroid nodules. Imaging studies showed collapse of left upper lobe. Fiberoptic bronchoscopy unveiled an endoluminal lesion and bronchial biopsy displayed features of melanoma. She denied a history of melanoma or excision of lesions of skin, mucous membranes or the eye. A thorough evaluation including combined positron emission tomography with CT scan excluded other possible sites of primary melanoma, but there was a metastasis in a thoracic vertebra. Palliative radiotherapy of the spine was performed. Chemotherapy initiation with dacarbazine was postponed by the appearance of a malignant pleural effusion, confirmed by pleural fluid cytology. After four cycles chemotherapy was discontinued due to disease progression. The patient is still alive with a follow-up of 12 months, currently on best supportive care.